2010
DOI: 10.3324/haematol.2009.020826
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the ribosomal protein genes in Japanese patients with Diamond-Blackfan anemia

Abstract: BackgroundDiamond-Blackfan anemia is a rare, clinically heterogeneous, congenital red cell aplasia: 40% of patients have congenital abnormalities. Recent studies have shown that in western countries, the disease is associated with heterozygous mutations in the ribosomal protein (RP) genes in about 50% of patients. There have been no studies to determine the incidence of these mutations in Asian patients with Diamond-Blackfan anemia. Design and MethodsWe screened 49 Japanese patients with Diamond-Blackfan anemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 27 publications
7
45
0
4
Order By: Relevance
“…15 This suggests ethnic differences in phenotypic expression; a feature that has been observed previously in other genetic diseases including Fanconi anemia. It also highlights the need to define the clinical-genetic spectrum in different ethnic populations.…”
Section: Diamond-blackfan Anemiamentioning
confidence: 58%
“…15 This suggests ethnic differences in phenotypic expression; a feature that has been observed previously in other genetic diseases including Fanconi anemia. It also highlights the need to define the clinical-genetic spectrum in different ethnic populations.…”
Section: Diamond-blackfan Anemiamentioning
confidence: 58%
“…Konno et al screened 49 Japanese patients and found that 30% (12 of 49) carried mutations. 8 In addition, our data showed that 22 of 68 DBA patients (32.4%) harbored a mutation in ribosomal protein (RP) genes (T.T., K.T., R.W., and E.I., unpublished observation, April 16, 2011). These abnormalities of RP genes cause defects in ribosomal RNA processing, formation of either the large or small ribosome subunit, and decreased levels of polysome formation, [4][5][6][9][10][11][12] which is thought to be one of the mechanisms for impairment of erythroid lineage differentiation.…”
Section: Introductionmentioning
confidence: 84%
“…Interestingly, mutations in RPS17 have been observed at a high rate (5.9%) in Japan relative to that in other countries (1%). 5,15,16 Although the percentage of DBA mutations differs among different ethnic groups, 8,[17][18][19] a certain portion of large deletions in DBA-responsible genes are likely to be determined in other countries by new strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 68 Japanese been examined, mutations in RPS 19, RPL5, RPL11, RPS17, RPS26 were identified in 10 (14.7 %), six (8.8 %), three (4.4 %), one (1.5 %), one (1.5 %), and one (1.5 %), respectively. These mutations have subsequently been determined to occur in 32.4 % of Japanese patients [25,26]. A low incidence of mutations in the RPS19 gene may account for the overall lower incidence of total mutations in the Japanese population.…”
Section: Molecular Pathogenesismentioning
confidence: 99%